Design and application of sporopollenin microcapsule supported palladium catalyst: Remarkably high turnover frequency and reusability in catalysis of biaryls - Baran, Talat; Sargın, İdris; Kaya, Murat; Menteş, Ayfer; Çeter, Talip (Elsevier BV, 2017)
Bio-based catalyst support materials with high thermal and structural stability are desired for catalysts systems requiring harsh conditions. In this study, a thermally stable palladium catalyst (up to 440°C) was designed from sporopollenin, which occurs naturally in the outer exine layer of pollens and is widely acknowledged as chemically very stable and inert biological material. Catalyst design procedure included (1) extraction of sporopollenin microcapsules from Betula pendula pollens (∼25μm), (2) amino-functionalisation of the microcapsules, (3) Schiff base modification and (4) preparation of Pd(II) catalyst. The catalytic activity of the sporopollenin microcapsule supported palladium catalyst was tested in catalysis of biaryls by following a fast, simple and green microwave-assisted method. We recorded outstanding turnover number (TON: 40,000) and frequency (TOF: 400,000) for the catalyst in Suzuki coupling reactions. The catalyst proved to be reusable at least in eight cycles. The catalyst can be suggested for different catalyst systems due to its thermal and structural durability, reusability, inertness to air and its eco-friendly nature.
Keywords: Schiff Base; Capsules; Chemistry Techniques, Synthetic; Anisoles; Boronic Acids; Carotenoids; Catalysis; Betula Pendula; Suzuki Coupling Reaction; Biopolymers; Silylation; Equipment Reuse; Pollen; Microwaves; Betula; Palladium; Schiff Bases